2014
DOI: 10.2135/cropsci2014.03.0177
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Breeding Andean Common Bean for Resistance to Common Bacterial Blight

Abstract: Common bacterial blight is a severe disease of common bean (Phaseolus vulgaris L.) worldwide. Use of resistant cultivars is crucial for its control. The objectives were to (i) assess the progress made in breeding large‐seeded Andean bean developed between 1974 and 2010 and (ii) determine their resistance‐linked sequence characterized amplified region (SCAR) marker composition. Ten Andean and four Middle American common bacterial blight resistant beans including checks were evaluated in the greenhouse in 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Each genotype was tested by PCR for the presence of the SCAR markers BC420, SAP6 and SU91 (Yu et al 2004;Duncan et al 2012;Viteri et al 2014) and the SSR marker PVctt001 (Yu et al 2000b;Michaels et al 2006), which are associated with resistance to CBB. DNA extraction and PCR assays were conducted as previously described by Boersma et al (2013).…”
Section: Pcr Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each genotype was tested by PCR for the presence of the SCAR markers BC420, SAP6 and SU91 (Yu et al 2004;Duncan et al 2012;Viteri et al 2014) and the SSR marker PVctt001 (Yu et al 2000b;Michaels et al 2006), which are associated with resistance to CBB. DNA extraction and PCR assays were conducted as previously described by Boersma et al (2013).…”
Section: Pcr Conditionsmentioning
confidence: 99%
“…However, Duncan et al (2012) determined that under severe disease pressure, SU91 alone did not provide high levels of CBB resistance and the combination of SU91 and BC420 was associated with high levels of CBB resistance. Viteri et al (2014) reported that certain bean cultivars which possessed the SCAR marker SU91 for CBB resistance displayed intermediate levels of CBB resistance and therefore they recommended pyramiding QTLs for resistance. However in the current study, the presence of both SU91 and BC420 along with SAP6 did not prevent substantial yield losses in HR67 caused by CBB.…”
Section: Qtl Markersmentioning
confidence: 99%
See 3 more Smart Citations